Changes in stroke parameters during the straight phase due to fatigue for elite female long distance speed skaters - Kimura, Y.; Yokozawa, T.; Kobai, H.; Yuda, J. (The Journal of Physical Fitness and Sports Medicine, 2018)
[Aims] The purpose of this study was to identify the characteristics of the changes in the stroke parameters during the straight phase due to fatigue for elite female long distance speed skaters.[Methods] The performances of 16 world-class elite female speed skaters who participated in official 3000-m races were recorded with four synchronized high-speed video cameras (300 fps) in the mid portion of a straight track by using the panning direct linear transformation technique. Three-dimensional coordinates of the body and blades during the initial, middle, and final sections of the races were collected to calculate stroke parameters. The skaters were divided into top (n = 8) and second groups (n = 8) according to the results of the official races. [Results] The horizontal velocities of the center of mass of the top group during the middle and final sections were significantly greater than those of the second group. In addition, the horizontal velocity of the center of mass of the second group significantly decreased throughout the race. No significant difference in cycle frequency was found between the top and second groups during each section. [Conclusions] Maintaining the horizontal velocity of the center of mass during the straight phase in the middle section would be an effective factor for enhancing the performance in the female long distance race.